Aeroacoustics Simulations around Automobile Rear-View Mirrors - Yoshihiro KATO; Igor MEN'SHOV; Yoshiaki NAKAMURA (Journal of Fluid Science and Technology, 2008)
A method for performing aeroacoustic simulation, in which the acoustic field is split from the flow field, is applied to the flow around automobile rear-view mirrors placed on a large solid plane. The flow can be obtained by performing large eddy simulation for the incompressible flow equations on colocated grids, while the acoustic equations are defined by the difference between the compressible and the incompressible flow equations, and solved by the finite volume method with the fourth order WENO scheme. The non-reflecting boundary conditions with a perfectly matched layer are applied to the outer boundary. Calculated results show clear sound emissions, where acoustic streamlines depict the propagation path based on acoustic intensity vectors. In this paper, two kinds of mirror shape, i.e., the cases with and without a strong vortex at the tip of the rear-view mirror, are compared. Calculated results show some differences between them in the acoustic field. The sound pressure related to the pressure frequency of the generated vortex is increased in all directions, though the propagation path does not show a large difference except near part of the body surface.